Translating humorous literature from Vietnamese into Italian language: an empirical study of humour reception - Thuy Hien Le (The European Journal of Humour Research, 2022)
The empirical study presented in this article aims to determine some of the linguistic and cultural elements that can influence the production process and the reception of humour and to verify the applicability of the General Theory of Verbal Humor (GTVH) to humorous literary translation. 60 Vietnamese and 60 Italian participants had to read and rate the level of humorousness of excerpts taken from the Vietnamese novel Số Đỏ (Vũ Trọng Phụng, 1936) and its correspondent Italian translation (Il gioco indiscreto di Xuan, 2012). By comparing their feedback, it was possible to observe that one is more likely to appreciate humour when one is not part of the categories subject to ridicule/irony/satire; and that a direct contact with the original language and culture constitutes an important role in humour understanding and appreciating. Also, a comparison between the rating that the Italian participants assigned to the official Italian translation and an alternative version allowed us to analyze the role of Language Knowledge Resource (GTVH). According to the Italian participants, although the two versions of the translation, which share the first five levels of Knowledge Resources, were remarkably similar (as predicted by the GTVH), they were dissimilar in terms of humour and in readers' preferences. I therefore argue that, although the GTVH is a useful tool for analyzing and verifying the similarity between the source and target text, it has proved to be impractical and not always reliable if we want to use it as a parameter of the translation of literary humorous texts.